2019
DOI: 10.4097/kja.d.18.00346
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the IPACK (Infiltration between the Popliteal Artery and Capsule of the Knee) block into a multimodal analgesic pathway for total knee replacement

Abstract: Background The Infiltration between the Popliteal Artery and Capsule of the Knee (IPACK) block is a new anesthesiologist- administered analgesic technique for controlling posterior knee pain that has not yet been well studied in total knee arthroplasty (TKA) patients. We compared pain outcomes in TKA patients before and after implementation of the IPACK with the hypothesis that patients receiving IPACK blocks will report lower pain scores on postoperative day (POD) 0 than non-IPACK patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 24 publications
1
41
3
1
Order By: Relevance
“…It has been reported that an adductor canal block can effectively control the anterior and medial pain in the knee joint by blocking the saphenous nerve, but the effect is not sufficient for controlling moderate to severe pain after TKA, especially for the control of pain in the posterior of the knee [ 18 , 19 ]. By blocking the sensory branches behind the knee joint, the IPACK block seemed to be a powerful and lasting method (effective analgesic time of a single IPACK block is 8–12 h) to control the pain behind the knee without affecting the muscle strength below the knee, which was conducive to early postoperative functional exercise [ 20 , 21 ]. In this study, patients in the ERAS group were treated with an ultrasonic-guided adductor canal block combined with IPACK block to achieve precise anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that an adductor canal block can effectively control the anterior and medial pain in the knee joint by blocking the saphenous nerve, but the effect is not sufficient for controlling moderate to severe pain after TKA, especially for the control of pain in the posterior of the knee [ 18 , 19 ]. By blocking the sensory branches behind the knee joint, the IPACK block seemed to be a powerful and lasting method (effective analgesic time of a single IPACK block is 8–12 h) to control the pain behind the knee without affecting the muscle strength below the knee, which was conducive to early postoperative functional exercise [ 20 , 21 ]. In this study, patients in the ERAS group were treated with an ultrasonic-guided adductor canal block combined with IPACK block to achieve precise anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The pain management protocol began the night before surgery with 1 g acetaminophen oral acetaminophen, and continued the day of surgery with another 1 g acetaminophen and 400 mg celecoxib. All patients received an adductor canal and IPACK block (Infiltration between the Popliteal Artery and Capsule of the Knee) in the preoperative waiting area as well as hypotensive anesthesia and a tourniquet during surgery [14]. Prior to the completion of the case, all patients receive a pericapsular block of ropivacaine plus epinephrine, and ketorolac if not renal impaired.…”
Section: Nomentioning
confidence: 99%
“…[ 9 ] Therefore, ultrasound-guided IPACK block seems to provide a promising motor-sparing posterior knee analgesia while reducing the possibility of nerve or vascular injury. [ 10 , 11 ]…”
Section: Introductionmentioning
confidence: 99%